Peran UMKM (Usaha Mikro, Kecil, Dan Menengah) Dalam Meningkatkan Pembangunan Ekonomi Di Indonesia - Putri Salsabila Indrawan Lubis; Rofila Salsabila (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
There are various classes for firms in Indonesia, according legal rules. Businesses can be classified into four categories: enormous, micro, small, and medium. The government refers to the three primary categories of businesses as UMKM, or micro, small, and medium enterprises. For this reason,